Promotion of Weather Resilient Technologies, Practices, and Services for Vegetables - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
India is the second-largest producer of vegetables in the world, though farmers face many challenges in vegetable cultivation. Selecting the right variety of seeds for vegetable crops like tomato, cucumbers, okra among others, and protecting the crops from the diseases, weeds, and insect pests are some of the major issues which the farmers of the project area faced. Based on the need assessment a portfolio of interventions was introduced to assist vegetable farmers in increasing their production and income. The case study shows that 464 farmers in Madhya Pradesh adopted improved / resilient practices, services, and technologies for vegetable cultivation.